CLINICAL EVALUATION OF SHUNTHYADI KWATHA AND TRIVIKRAM RAS IN THE MANAGEMENT OF MOOTRAASHMARI (UROLITHIASIS) (International Journal of Food and Nutritional Sciences, 2021)
Ayurveda, is the system of Indian medicine and science of life which deals with the wellbeing of mankind, it explains all the aspects of diseases like causes, types, treatment etc of many diseases, the disease of urinary stone is explained under the heading of Mootraashmari. The reference regarding it can be found in all most all the Samhitas, Acharya Sushruta has described nidana, samprapti, laxanas, chikitsa etc in most scientific manner in separate chapter. Objectives of the study is to evaluate the efficacy of Trivikram rasa in the management of mootraashmari. Study Design: open labelled clinical study. Patients of diagnosed with mootraashmari satisfying inclusion criteria was included in study from OPD and IPD of Nitishwar Ayurveda Medical College & Hospital & P. G. Research Institute, Muzaffarpur 841226, (Bihar) India. They registered under different groups for the assessment of effect of Shunthyadi Churna and Trivikram ras on Mootraashmari also called as Urolithiasis. Based on the assessment criteria the parameters are graded and statistically analysed using Paired t‟ test. Results: In this study, the subjective and objective parameter shows significant results. As the drug caused reduction in size of calculus in some patients and even expulsion of calculus in some others, hence bypassed the operative procedures this drug can be considered as cost effective and safe regarding management of calculus.